Cerebrospinal fluid characteristics of patients presenting for evaluation of pediatric acute-neuropsychiatric syndrome - Pooni, Rajdeep; Zheng, Wynne; Ma, Meiqian; Silverman, Melissa; Xie, Yuhuan; Farhadian, Bahare; Thienemann, Margo; Mellins, Elizabeth; Frankovich, Jennifer (Frontiers in Behavioral Neuroscience, 2024)
Objectives This study characterizes cerebral spinal fluid (CSF) indices including total protein, the albumin quotient, IgG index and oligoclonal bands in patients followed at a single center for pediatric acute-neuropsychiatric syndrome (PANS) and other psychiatric/behavioral deteriorations. Methods In a retrospective chart review of 471 consecutive subjects evaluated for PANS at a single center, navigational keyword search of the electronic medical record was used to identify patients who underwent lumbar puncture (LP) as part of the evaluation of a severe or atypical psychiatric deterioration. Psychiatric symptom data was ascertained from parent questionnaires and clinical psychiatric evaluations. Inclusion criteria required that subjects presented with psychiatric deterioration at the time of first clinical visit and had a lumbar puncture completed as part of their evaluation. Subjects were categorized into three subgroups based on diagnosis: PANS (acute-onset of severe obsessive compulsive disorder (OCD) and/or eating restriction plus two other neuropsychiatric symptoms), autoimmune encephalitis (AE), and “other neuropsychiatric deterioration” (subacute onset of severe OCD, eating restriction, behavioral regression, psychosis, etc; not meeting criteria for PANS or AE). Results 71/471 (15.0 %) of patients underwent LP. At least one CSF abnormality was seen in 29% of patients with PANS, 45% of patients with “other neuropsychiatric deterioration”, and 40% of patients who met criteria for autoimmune encephalitis. The most common findings included elevated CSF protein and/or albumin quotient. Elevated IgG index and IgG oligoclonal bands were rare in all three groups. Conclusion Elevation of CSF protein and albumin quotient were found in pediatric patients undergoing LP for evaluation of severe psychiatric deteriorations (PANS, AE, and other neuropsychiatric deteriorations). Further studies are warranted to investigate blood brain barrier integrity at the onset of the neuropsychiatric deterioration and explore inflammatory mechanisms.